2015
DOI: 10.1038/jcbfm.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Agent CNTF Decreases Neuronal Metabolites in the Rat Striatum: An in Vivo Multimodal Magnetic Resonance Imaging Study

Abstract: Ciliary neurotrophic factor (CNTF) is neuroprotective against multiple pathologic conditions including metabolic impairment, but the mechanisms are still unclear. To delineate CNTF effects on brain energy homeostasis, we performed a multimodal imaging study, combining in vivo proton magnetic resonance spectroscopy, high-performance liquid chromatography analysis, and in situ glutamate imaging by chemical exchange saturation transfer. Unexpectedly, we found that CNTF expression through lentiviral gene transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The reduction in the GluCEST signal in encephalitis lesions after treatment may be due to the fact that the activation of microglia or pro-inflammatory factors was inhibited by immunoglobulin. This result is consistent with a similar previous study that reported a reduced GluCEST signal following ciliary neurotrophic factor (CNTF) injection in the brain, which was attributed to reduced astroglial cellular activity as well as a reduction in the level of glutamine, a precursor of Glu (Carrillo-De Sauvage et al, 2015). Of course, the detailed mechanism of Glu in encephalitis requires further study.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in the GluCEST signal in encephalitis lesions after treatment may be due to the fact that the activation of microglia or pro-inflammatory factors was inhibited by immunoglobulin. This result is consistent with a similar previous study that reported a reduced GluCEST signal following ciliary neurotrophic factor (CNTF) injection in the brain, which was attributed to reduced astroglial cellular activity as well as a reduction in the level of glutamine, a precursor of Glu (Carrillo-De Sauvage et al, 2015). Of course, the detailed mechanism of Glu in encephalitis requires further study.…”
Section: Discussionsupporting
confidence: 93%
“…Development of non-invasive imaging techniques, like magnetic resonance imaging (MRI) or positron emission tomography (PET) to visualize when and where astrocytes become reactive would help disease diagnostic. Available imaging methods are not quite specific for reactive astrocytes, they rather detect neuroinflammation as a whole (i.e., reactive glial cells, sometimes infiltration of peripheral immune cells) or associated changes, for example, in brain metabolism (Aiello et al, 2018;Carrillo-de Sauvage et al, 2015;Lavisse et al, 2012).…”
Section: Why Bother With Reactive Astrocytes?mentioning
confidence: 99%
“…Interestingly, reactivity can be selectively induced in astrocytes, leaving microglial cells virtually unaffected, by overexpressing the cytokine CNTF (Lavisse et al, 2012 ), or through the genetic ablation of β1-integrin in astrocytes (Robel et al, 2009 ). Such approaches have contributed to identify functional changes occurring in reactive astrocytes, including changes in glutamate homeostasis (Escartin et al, 2006 ; Beurrier et al, 2010 ), energy metabolism (Escartin et al, 2007 ; Carrillo-De Sauvage et al, 2015 ) and K + homeostasis (Seidel et al, 2014 ; Robel et al, 2015 ); see Liberto et al ( 2004 ) for a general review.…”
Section: What Do Reactive Astrocytes Do or Fail To Do During Nd?mentioning
confidence: 99%
“…NMR-spectroscopy (MRS) allows the quantification of abundant brain metabolites, including myo-inositol, glutamine and choline which are enriched in glial cells. In a model of selective astrocyte reactivity in the rat brain, myo-inositol and choline levels are higher whereas glutamine levels are lower than in controls, suggesting that reactivity leads to the complex re-structuring of metabolic pathways (Carrillo-De Sauvage et al, 2015 ). High concentrations of myo-inositol are also commonly observed in ND models and patients, which correlates with neuroinflammation (Choi et al, 2007 ).…”
Section: Ongoing Questions Future Directionsmentioning
confidence: 99%